Preparing and Reporting Income Tax - Anjelina Anjelina; Kisah Naomi Claudia Sitorus (Journal of Applied Accounting and Taxation, 2016)
The purpose of the study is to know and understand the preparation, paying, and reporting of Income Tax Article 23 on the use of services. The survey results revealed that the withholding and tax calculations performed by sample company has been in accordance with provisions contained in UU No. 36 of 2008 and Peraturan Menteri Keuangan Republik Indonesia Nomor 141/PMK.03/2015, but there is a difference between the period of preparation withholding tax (PPh) and payment transactions of the company. There is a difference that occurs due to inaccuracy withholding taxes. This led to a tax credit or the amount of tax payments paid a period is greater than the amount that should have been by company.